Implikasi Hukum Ketidakterpenuhan Syarat Subjektif dalam Pasal 1320 Kitab Undang-Undang Hukum Perdata terhadap Keabsahan Perjanjian - Susi Sopiani; Vika Nur Senda; Mochamad Fajar Muzzamil (Letterlijk, 2024)
According to article 1 paragraph 3 of the 1945 Constitution of the Republic of Indonesia, it is stated that Indonesia is a legal state. In social life, agreements play a very important role as a legal instrument that regulates relationships between individuals and between institutions. According to article 1313 of the Civil Code which reads, "An agreement is an act by which one or more people bind themselves to one or more other people. Fulfilling the subjective requirements in making an agreement according to Article 1320 of the Civil Code is very important to ensure the validity of the agreement. Failure to comply with these conditions can have serious legal implications, including cancellation of the agreement or a declaration that the agreement was invalid from the start. The author uses a type of juridical normative research method, by examining library materials or secondary data which includes, among other things, primary legal materials, secondary legal materials and tertiary legal materials. The result that can be concluded is that non-fulfillment of these subjective conditions makes the agreement revocable (vernietigbaar), which means the agreement remains in effect until an interested party requests its cancellation in court. Implications for the rights and obligations of the parties occur if the agreement is canceled due to non-fulfillment of subjective conditions, then the rights and obligations of the parties will follow the legal consequences of the cancellation.